O1-S07.06 Lymphogranuloma venereum in the UK: is there evidence for rectal to rectal transmission? Results of a multicenter case control study. (10th July 2011) - Ward, H; Macdonald, N; Ronn, M; Dean, G; Pallawela, S; Sullivan, A; White, J; Smith, A; French, P; Ison, C
Abstract : Background: The outbreak of lymphogranuloma venereum (LGV) in men who have sex with men (MSM) in the UK is ongoing, with over 500 cases diagnosed in 2010 alone. Control efforts have been limited by a lack of understanding of the epidemiology, particularly transmission. The majority of cases are rectal with small numbers of urogenital or pharyngeal infections. No significant reservoir of asymptomatic or undiagnosed infection has been identified. The possibility of rectal to rectal transmission is suggested by studies showing an association of LGV with fisting, use of sex toys and enemas. We aim to identify risk factors to better understand transmission. Methods: A case control study of LGV in six UK clinics from 2009 to the end of 2010. Confirmed cases of LGV in MSM were compared with symptomatic and asymptomatic controls. Clinical and behavioural data were collected using a web-based computer-assisted self-interview and linked to web-based clinical report forms (CRF). We used a two-stage process to construct multivariable logistic regression models in order to control for confounding and interaction between risk factors. Results: We have recruited 99 cases, 86 symptomatic and 88 asymptomatic controls. There were 94 rectal cases (including one who also had pharyngeal LGV), two urethral and one genital ulcer (two CRFs outstanding). In univariate analysis, LGV was significantly associated with many factors; the strongest associations were with HIV infection, specific anal sex practices (including unprotected receptive and insertive intercourse, rimming, use of toys, fisting, douching), meeting partners through the internet or in a backroom, and use of stimulant drugs. In final multivariable logistic regression models HIV-positivity, fisting, younger age at first clinic attendance and recent use of methamphetamine remained significant predictors of LGV when compared to asymptomatic controls. Compared to symptomatic controls, unprotected insertive anal intercourse was the only significant risk factor in the final model. Conclusions: Men reporting both insertive and receptive anal sex practices are at highest risk of LGV. Rectal to rectal transmission may be occurring with the organism being transferred via toys, fingers and penises; transient colonisation of the urethra may explain the low incidence of urethral LGV. Improved hygiene measures may have an important role in reducing transmission.